2017
DOI: 10.1016/j.cub.2017.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Jitter Perceived at the Frequency of Alpha Oscillations

Abstract: Neural oscillations, such as alpha (8-13 Hz), beta (13-30 Hz), and gamma (30-100 Hz), are widespread across cortical areas, and their possible functional roles include feature binding [1], neuronal communication [2, 3], and memory [1, 4]. The most prominent signal among these neural oscillations is the alpha oscillation. Although accumulating evidence suggests that alpha oscillations correlate with various aspects of visual processing [5-18], the number of studies proving their causal contribution in visual pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 52 publications
6
111
0
Order By: Relevance
“…They showed 72 that the EEG response to the stimulation depends on both the stimulation intensity and the distance 73 between the flicker frequency and the participants' individual alpha frequency (IAF; Notbohm et al, 74 2016). Other studies found similar effects for tACS over occipital cortex which either increases EEG 75 power at participants' visual alpha frequency (Helfrich et al, 2014;Zaehle, Rach, & Herrmann, 2010), 76 or biases ongoing alpha oscillations in visual cortex towards the exogenous stimulation frequency 77 (Minami & Amano, 2017). Most previous studies have tested entrainment in visual cortex targeting 78 the alpha rhythm.…”
mentioning
confidence: 82%
“…They showed 72 that the EEG response to the stimulation depends on both the stimulation intensity and the distance 73 between the flicker frequency and the participants' individual alpha frequency (IAF; Notbohm et al, 74 2016). Other studies found similar effects for tACS over occipital cortex which either increases EEG 75 power at participants' visual alpha frequency (Helfrich et al, 2014;Zaehle, Rach, & Herrmann, 2010), 76 or biases ongoing alpha oscillations in visual cortex towards the exogenous stimulation frequency 77 (Minami & Amano, 2017). Most previous studies have tested entrainment in visual cortex targeting 78 the alpha rhythm.…”
mentioning
confidence: 82%
“…Interestingly, the DAC itself 321 exhibited comparatively weak artifacts, while the more complex setups showed stronger 322 artifacts at the modulation frequency and several harmonics. This might indicate that the effect 323 is driven by non-linearities of the stimulator or recording hardware rather than the DAC as 324 suggested by previous authors (Minami and Amano, 2017). 325…”
Section: Discussion 301mentioning
confidence: 83%
“…Consequently, the tACS artifact would be shifted into higher frequencies, elegantly 81 avoiding spectral overlap with the targeted brain oscillation. However, more recently low-fre-82 quency artifacts at have been reported in sensor-level MEG recordings during AM-tACS 83 (Minami and Amano, 2017). These artifacts required the application of advanced artifact sup-84 pression algorithms (Minami and Amano, 2017).…”
Section: Introduction 46mentioning
confidence: 99%
See 2 more Smart Citations